2015
DOI: 10.1016/j.bbrc.2015.07.137
|View full text |Cite
|
Sign up to set email alerts
|

GABAB receptors inhibit low-voltage activated and high-voltage activated Ca2+ channels in sensory neurons via distinct mechanisms

Abstract: Abbreviations: DRG, dorsal root ganglion; DTT, dithiothreitol; GABA, gamma-aminobutyric acid; GFP, green fluorescent protein; HEK293, human embryonic kidney 293 cells; HVA, high voltage activated Ca 2+ channels; LVA, low voltage activated Ca 2+ channels; NK1, neurokinin receptor isoform 1; ROS, reactive oxygen species; PTX, pertussis toxin; VGCC, voltage-gated Ca 2+ channels Abstract Growing evidence suggests that mammalian peripheral somatosensory neurons express functional receptors for gamma-aminobutyric ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…As reported by other groups, this receptor distribution may coordinate GABAergic regulation of intestinal motility, gastric emptying, gastric acid secretion, and transient lower esophageal sphincter relaxation . Interestingly, a recent in vitro study showed that the GABA agonist baclofen decreased DRG neuron activity by acting on GABA B receptors and inhibiting both low‐voltage activated and high‐voltage activated Ca 2+ currents . γ ‐aminobutyric acid has also recently been shown to act via the GABA B1 receptor on peripheral nociceptive terminals to modulate nociceptor sensitization and counteract inflammatory pain via interaction with the pain receptor, TRPV1 .…”
Section: Discussionsupporting
confidence: 52%
“…As reported by other groups, this receptor distribution may coordinate GABAergic regulation of intestinal motility, gastric emptying, gastric acid secretion, and transient lower esophageal sphincter relaxation . Interestingly, a recent in vitro study showed that the GABA agonist baclofen decreased DRG neuron activity by acting on GABA B receptors and inhibiting both low‐voltage activated and high‐voltage activated Ca 2+ currents . γ ‐aminobutyric acid has also recently been shown to act via the GABA B1 receptor on peripheral nociceptive terminals to modulate nociceptor sensitization and counteract inflammatory pain via interaction with the pain receptor, TRPV1 .…”
Section: Discussionsupporting
confidence: 52%
“…9 In laminae I-II, electrophysiological studies performed in rat demonstrated that the exogenous or endogenous activation of presynaptic GABA B Rs inhibits the release of peptides and glutamate from the primary afferent terminals of Aδ and C types 5,1014 and decreases the release of GABA and glycine from the spinal inhibitory interneurons. 1416 The depression of neurotransmitter release mediated by GABA B Rs derives from the concurrent inhibition of presynaptic calcium channels 1719 and release machinery downstream Ca 2+ entry into the nerve terminals. 20 …”
Section: Introductionmentioning
confidence: 99%
“…This redox modulation of Cav3.2 channels could also be involved in the GABA B receptor inhibition of T‐type channels in DRG neurons (Huang et al . ). Of interest, it was recently reported that chelating zinc with TPEN could facilitate modulation of GABAergic inhibitory post‐synaptic currents in hippocampal granule cells, an effect that was occluded when blocking T‐type channels (Grauert et al .…”
Section: Discussionmentioning
confidence: 97%
“…In addition, other studies have suggested that the endogenous gasotransmitters, such as hydrogen sulfide (H 2 S) and carbon monoxide (CO), could also play a role in Cav3.2 channel regulation through redox-related mechanisms involving H191 (Boycott et al 2013;Elies et al 2014;Sekiguchi et al 2014). This redox modulation of Cav3.2 channels could also be involved in the GABA B receptor inhibition of T-type channels in DRG neurons (Huang et al 2015). Of interest, it was recently reported that chelating zinc with TPEN could facilitate modulation of GABAergic inhibitory post-synaptic currents in hippocampal granule cells, an effect that was occluded when blocking T-type channels (Grauert et al 2014).…”
Section: Metal/redox Sensitivity Of T-type Currents In Drg Neurons mentioning
confidence: 99%